The Impact of Digital Inclusive Finance on Agricultural Green Total Factor Productivity: Evidence From China - Gao, Qiang; Cheng, Changming; Sun, Guanglin; Li, Jianfeng (Frontiers in Ecology and Evolution, 2022)
This paper applies the GML model with unexpected output to measure agricultural green total factor productivity (GTFP) in 30 provinces in China from 2011 to 2019. We explore the effect and mechanism of digital inclusive finance (DIF) on agricultural green total factor productivity. Our empirical results show that during the sample period, China's agricultural green total factor productivity has shown an increasing trend. Digital inclusive finance mainly promotes agricultural GTFP by improving green technology level. The coverage rate, the application rate and the digitalization rate of digital inclusive finance all generate positive effects on agricultural green total factor productivity, among which the coverage rate contributes the most. Besides, the positive effect of digital inclusive finance in the eastern coastal areas is more significant than in other areas. The analysis of the mechanism shows that digital inclusive finance can indirectly help improve agricultural green total factor productivity through motivating agricultural technology innovation and industrial structure optimization. The research results of this paper are extremely meaningful for better implement DIF-related policies, and promote the green development of agriculture.